Investigation on the surface discharge phenomenon at the oil-pressboard interface - Zainuddin, Hidayat; Lewin, P.L.; Mitchinson, P.M. (2011)
Surface discharge on the oil-pressboard interface is considered to be serious fault condition. This phenomenon leads to the formation of a conducting path on the surface of an insulation material as a result of surface currents. The surface current is effectively the drift of charge under the action of an electric field which may be either the general electric field or a locally enhanced field developed around a space charge. Sustained surface discharge can eventually result in equipment failure. A needle-bar electrode configuration has been used to investigate the surface discharge phenomenon at the oil pressboard interface. This paper presents the partial discharge (PD) patterns corresponding to the surface discharge events.